Re-evaluation of the environmental hazards of nZnO to denitrification: Performance and mechanism. (March 2022) - Ma, Xiao-Lin; He, En-Jing; Cao, Feng-Ting; Fan, Yang-Yang; Zhou, Xiang-Tong; Xiao, Xiang
Abstract: Numerous studies have shown that zinc oxide nanoparticles (nZnO) have an inhibitory effect on wastewater biotreatment, where doses exceeding ambient concentrations are used. However, the effect of ambient concentrations of ZnO (<1 mg/L) on anaerobic digestion processes is not clear. Herein, this study comprehensively explored the impact of nZnO on the denitrification performance and core microbial community of activated sludge under ambient concentrations. Results showed that only 0.075 mg/L nZnO had shown a beneficial effect on nitrogen removal by activated sludge. When nZnO concentration reached 0.75 mg/L, significant enhancement of nitrate reduction and mitigation of nitrite accumulation were observed, indicating a remarkable stimulatory effect on nitrogen removal. Simultaneously, nZnO could weaken the sludge surface charge and improve the secretion of extracellular polymeric substances, thus enhancing sludge flocculation for denitrification. Microbial community analysis revealed that nZnO exposure increased the relative abundance of denitrifying bacteria, which could contribute to the reinforcement of traditional denitrification. Furthermore, exogenous addition of NH4 + significantly inhibited the accumulation of nitrite, implying that nZnO had a potential to improve the denitrification process via a partial denitrification-anammox pathway. Considering current ambient concentration, the stimulatory effect shown in our work may better represent the actual behavior of ZnO in wastewater biotreatment. Graphical abstract: Image 1 Highlights: Low-concentration nZnO stimulated the anaerobic denitrification of activated sludge. Traditional denitrification pathway dominated the enhanced denitrification by nZnO. Exogenous addition of NH4 + improved nitrate removal under nZnO exposure. NZnO exposure influenced the zeta potential and EPS production of activated sludge. NZnO contributed to the relative abundance of denitrifying bacteria.